A novel fluorescent lung-marking technique using the photodynamic diagnosis endoscope system and vitamin B2. (17th September 2020) - Tanaka, Nobuhiro; Waseda, Ryuichi; Saito, Daisuke; Ohsima, Masahiro; Matsumoto, Isao; Takemura, Hirofumi
Abstract: OBJECTIVES: For small pulmonary nodules that are unidentifiable by palpation or in endoscopic surgeries wherein palpation is not feasible, visualizing their location is necessary when performing pulmonary sublobar resection procedures, such as wedge resection or segmentectomy. We invented a new transbronchial lung-marking technique using the photodynamic diagnosis endoscope system and vitamin B2 and examined its feasibility and safety via porcine studies. METHODS: We established the marking procedure in pigs and examined the marking clarity and size, fluorescence intensity and duration and possible complications. In another study, sublobar resection for virtual target lesions was performed in pigs based on the fluorescent markings. The procedure duration, marking visibility, surgical margin from the lesions and technique-related complications were assessed. RESULTS: All 36 markings in 6 pigs were identifiable and were widely distributed over the right lung. The median diameter and fluorescence intensity at 60 min after marking were 6.0 (5.5–6.7) mm and 137.5 (122–168), respectively. All 18 markings for the 6 virtual target lesions (3 markings for each target) were clearly identified, and all target lesions were found in the resected specimens. The median duration per marking was 244 (194–255) seconds. The shortest median surgical margin from a target lesion was 11.5 (9.3–13.5) mm. No procedure-related complications were observed. CONCLUSIONS: This novel transbronchial fluorescent lung-marking technique was useful and safe in sublobar resections for small non-palpable pulmonary lesions. Abstract : Advances in high-resolution computed tomography (CT) have facilitated small pulmonary nodule detection [1].